Sampling for household-based surveys of child labour - Verma, Vijay (ILO, 2008)
This manual presents a wide range of sampling techniques for household-based child labour surveys with a particular emphasis on sampling design and selection procedures. It is meant to assist survey professionals in statistical offices, universities and research organizations. Many of the concepts and approaches introduced by the Manual are illustrated with examples from SIMPOC child labour surveys conducted in all major world regions.